PRWformer: An interpretable transformer-based model for probabilistic regional wave forecasting - Jie Ding; Delei Li; Jiagen Wang; Guangming Fu; Jichao Wang (Ocean Engineering, 2026)

GAS6 Mediates Benzo[a]pyrene-Induced Pathological Cardiac Hypertrophy via the mTOR/HIF-1α Glycolytic Remodeling Axis - Guangming Li; Feihu Long; Zhiyue Liu; Jiarui Nicole Fu; Yuanyin Teng; Shanshan Cai; Xiaoling Zhang; Yingji Wang (Chemico-Biological Interactions, 2026)

New healthcare management framework informed by peri-body perception space: a perspective - Chaoqun Dong; Yan Ji; Ruzhen Luo; Xuemei Fu; Zhongmin Fu; Yingying Huang; Ting Yi; Zhifei Chen; Yiwen Hu; Ziqi Chen; Shimeng Dai; Guangming Tao; et al. (EPMA Journal, 2026)

Thermo-mechanically coupled damage constitutive model and cross-scale fracturing mechanisms in argillaceous sandstone - Jie Fu; Wensong Xu; Guangming Zhao; Yian Chen; Xiangrui Meng (Bulletin of Engineering Geology and the Environment, 2026)

Ultimate Axial Load Capacity of Production Tubular Strings in Offshore Extended-Reach Wells - Yanfei Li; Bin Cai; Junrui Ge; Hao Fu; Jian Wu; Penglei Tang; Lei Zuo; Zhengkang Li; Shuhan Liu; Guangming Fu (Journal of Marine Science and Engineering, 2026)
As oil and gas exploration advances, tubular strings in extended-reach wells are becoming increasingly susceptible to buckling, self-locking, and other failure modes due to their relatively low weight and limited structural stiffness. Existing studies have mainly focused on running feasibility and associated mechanical responses, whereas systematic investigations of the ultimate axial load capacity of deployed tubular strings remain limited. To address this research gap, the present study investigates the ultimate axial load capacity of tubular strings in deepwater extended-reach wells, explicitly accounting for the constitutive behavior of the tubular material. Numerical simulations were performed under both tensile and compressive loading conditions for different well trajectories, dogleg severities, material grades, and wellbore diameters, and the effects of these factors on the ultimate axial load capacity were systematically evaluated. The numerical predictions at the initial yielding stage were compared with available analytical solutions, and good agreement was obtained, indicating that the proposed model is reliable for initial yield analysis. The results show that well trajectory, dogleg severity, material grade, and wellbore diameter significantly influence the ultimate axial load capacity of tubular strings. The findings of this study provide useful guidance for structural integrity assessment, design optimization, and operating-parameter selection for downhole tubular strings in deepwater and ultra-deepwater oil and gas developments, thereby supporting the safe and efficient completion of extended-reach wells.

Empirical Formula for Estimating Collapse Pressure of Dented Sandwich Pipes - Zijian Zheng; Yihao Hu; Guangming Fu; Ming Song; Segen F. Estefen (Journal of Marine Science and Engineering, 2026)
Deepwater sandwich pipes (SPs) offer high collapse resistance and thermal insulation, making them promising for hydrocarbon transport under high-pressure and low-temperature conditions. However, mechanical damage such as local dents increases cross-sectional ovality and can substantially degrade their external pressure capacity. This study develops a numerical model using ABAQUS to assess the collapse pressure of dented deepwater SPs under hydrostatic loading. The model is validated against existing reference data. A total of 2316 FE models are constructed to investigate the effects of material properties, geometric configurations, and dent characteristics on collapse performance. Results show that the collapse pressure decreases significantly with increasing dent depth, and spherical dents have a more pronounced effect than planar dents. Enhanced collapse resistance is observed as both the thickness ratio and the core thickness of the sandwich structure increase. The use of higher-strength materials in the core layer and the internal and external layers also improves compressive capacity. Drawing on these results, a simplified formula for estimating the collapse pressure of dented sandwich pipes is proposed.

Enhanced LSHADE-SPACMA with fitness-directed selection pressure mutation and elastic archive for UAV trajectory planning and PV parameter identification - Wenhao Mao; Shengwei Fu; Guozhang Zhang; Haisong Huang; Guangming Gong; Yulu Liu; Honghai Fu; Yinwei Li; Yongpeng Zhao; Langlang Zhang; Jiawei Wang (Swarm and Evolutionary Computation, 2026)

Be–Nb–Ta metallogenesis in Himalayan leucogranites, China: trace element constraints from apatite in the Lalong Dome - Jiangang Fu; Guangming Li; Weikang Guo; Suiliang Dong; Linkui Zhang; Yingxu Li; Yanjie Jiao (Journal of Asian Earth Sciences, 2026)

Machine learning for spectral precision: a new horizon in radiative cooling material design - Xinpeng Hu; Mingxiang Liu; Xuemei Fu; Guangming Tao; Xiang Lu; Jinping Qu (Science Bulletin, 2025)

Activating graphitic carbon via a core/shell WO3/carbon architecture for electrocatalytic deactivation of dilute antibiotics - Wenyang Fu; Yanjun Yin; Jiahong Zou; Chunyang Dan; Shenbin Zheng; Huimin Sui; Yinan Liu; Yan Zou; Heng Shi; Guangming Jiang (Chemical Engineering Journal, 2025)

Anti-passivation Fe-Ni Foam@AC PRB: Coupling bimetallic electron transfer and functionalized adsorption for sustainable groundwater nitrate remediation - Guangming Li; Jiani Fu; Xiaomin Fu; Shuwen Zhu; Jie Dong; Wenpeng Jiang (Groundwater for Sustainable Development, 2025)

Characteristics and life cycle carbon emission reduction potential of waste recycling after implementing new waste classification policy in China: From case study to national perspective - Hao Fu; Le Chen; Wei Fang; Wenfang Gao; Kun Hu; Panyue Zhang; Guangming Zhang (Journal of Environmental Sciences, 2025)

Dynamic Behavior of a Rotationally Restrained Pipe Conveying Gas-Liquid Two-Phase Flow - Guangming Fu; Huilin Jiao; Aixia Zhang; Xiao Wang; Boying Wang; Baojiang Sun; Jian Su (Journal of Marine Science and Engineering, 2025)
This study explores the dynamic behavior of a vertical pipe conveying gas-liquid two-phase flow with rotationally restrained boundaries, employing the generalized integral transform technique (GITT). The rotationally restrained boundary conditions are more realistic for practical engineering applications in comparison to the classical simply-supported and clamped boundary conditions, which can be viewed as limiting scenarios of the rotationally restrained boundary conditions when rotational stiffness approaches zero and infinity, respectively. Utilizing the small-deflection Euler-Bernoulli beam theory, the governing equation of motion for the deflection of the pipe is transformed into an infinite set of coupled ordinary differential equations, which is then numerically solved following truncation at a finite order NW. The proposed integral transform solution was initially validated against extant literature results. Numerical findings demonstrate that as the gas volume fraction increases, there is a reduction in both the first-order critical flow velocity and the vibration frequency of the pipe conveying two-phase flow. Conversely, as the rotational stiffness factor enhances, both the first-order critical velocity and vibration frequency increase, resulting in improved stability of the pipe. The impact of the bottom-end rotational stiffness factor r2 on the dynamic stability of the pipe is more pronounced compared to the top-end rotational factor r1. The variation in two-phase flow parameters is closely associated with the damping and stiffness matrices. Modifying the gas volume fraction in the two-phase flow alters the distribution of centrifugal and Coriolis forces within the pipeline system, thereby affecting the pipeline’s natural frequency. The results illustrate that an increase in the gas volume fraction leads to a decrease in both the pipeline’s critical velocity and vibration frequency, culminating in reduced stability. The findings suggest that both the gas volume fraction and boundary rotational stiffness exert a significant influence on the dynamic behavior and stability of the pipe conveying gas-liquid two-phase flow.

High-temperature polymer electrolyte membrane electrochemical hydrogen pump challenging for hydrogen purification in fuel cycle of fusion device - Yiyang Zeng; Shuai Yang; Yu Gong; Xingrui Tang; Mao Yang; Xiaolong Fu; Junyan Wang; Guangming Ran; Chengjian Xiao (Chemical Engineering Journal, 2025)

Synergistic effects of bio-organic fertilizer and different soil amendments on salt reduction, soil fertility, and yield enhancement in salt-affected coastal soils - Meng Xiao; Shengguo Jiang; Jinbiao Li; Wenping Li; Pengxiao Fu; Guangming Liu; Jinlin Chen (Soil and Tillage Research, 2025)

Rice-straw-derived porous biochar with low spatial polarity for efficient adsorptive removal of antibiotics in surface water - Wei Fan; Linpiao Cheng; Wenyang Fu; Jianhui Liu; Guangming Jiang; Liang Ao (Journal of Water Process Engineering, 2025)

Electron beam irradiation coupled ultrasound-assisted natural deep eutectic solvents extraction: A green and efficient extraction strategy for proanthocyanidin from walnut green husk - Heting Qi; Wanjia Fu; Yujie Liu; Junqing Bai; Ruolin Wang; Guangming Zou; Heyu Shen; Yingying Cai; Anwei Luo (Food Chemistry, 2025)

Electrocatalytic conversion of nitrate to ammonia on the oxygen vacancy engineering of zinc oxide for nitrogen recovery from nitrate-polluted surface water - Wenyang Fu; Yanjun Yin; Shuxian He; Xiangyi Tang; Yinan Liu; Fei Shen; Yan Zou; Guangming Jiang (Environmental Research, 2025)

Assessing the discrepant role of anions in the transformation of reactive oxygen species in H2O2 and PDS system: A comparative kinetic analysis - Ling Li; Min Cheng; Hao Sun; Huan Yi; Shiyu Liu; Mingming Zhang; Yukui Fu; Xuerong Zhou; Fuhang Xu; Dengsheng Ma; Guangming Zeng; Zhengjian Yang; et al. (Journal of Hazardous Materials, 2024)

Activating copper by creating low-coordinated copper sites for antibiotic detoxification through Electrocatalytic hydrodechlorination reaction - Xiangyi Tang; Fei Shen; Wei Fan; Jianhui Liu; Lingpiao Chen; Yinan Liu; Liang Ao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Ling Chen; Yan Jiang; et al. (Chemical Engineering Journal, 2024)

Development and challenges of emerging biological technologies for algal-bacterial symbiosis systems: A review - Zhijun Ren; Huixue Li; Peng Sun; Ruiyao Fu; Zijia Bai; Guangming Zhang; Li Sun; Yanjie Wei (Bioresource Technology, 2024)

Cobalt single-site molecular Catalyst-mediated electrochemical Hydrodechlorination for detoxification of halogenated Antibiotics: Performance, reaction pathway and mechanism - Yinan Liu; Xiangyi Tang; Fei Shen; Jiahong Zou; Yanjun Yin; Zhaojie Jiao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Guangming Jiang; Hong Liu (Chemical Engineering Journal, 2024)

Efficient electrocatalytic nitrate reduction on molecular catalyst with electron-deficient single-atom Cuδ+ sites - Li Shi; Yiming Li; Shuxian He; Yinan Liu; Xiangyi Tang; Liang Ao; Xiaoshu Lv; Wenyang Fu; Guangming Jiang (Chemical Engineering Journal, 2024)

Life cycle assessment of n-caproic acid production via chain elongation from food waste: Comparison of shunting and staged technology - Qingyan Wang; Hao Fu; Wenfang Gao; Yajing Cai; Panyue Zhang; Guangming Zhang (Environmental Research, 2024)

Rational design of a rapidly responsive and highly selective fluorescent probe for SO2 derivatives detection and imaging - Shiyi Zhang; Xiaopeng Yang; Ying Xu; Haiyang Wang; Fei Luo; Guangming Fu; Dingwei Yan; Miao Lai; Yu Ke; Yong Ye; Xiaoming Ji (Food Chemistry, 2024)

Unraveling biological behavior and influence of magnetic iron-based nanoparticles in algal-bacterial systems: A comprehensive review - Zhijun Ren; Ruiyao Fu; Li Sun; Huixue Li; Zijia Bai; Yu Tian; Guangming Zhang (Science of The Total Environment, 2024)

An MINLP model for optimal sandwich pipe design based on structural and thermal criteria - Guangming Fu; Jiankun Yang; Marcelo I. Lourenço; Segen F. Estefen (Ocean Engineering, 2024)

Advances in understanding entire process of medium chain carboxylic acid production from organic wastes via chain elongation - Qingyan Wang; Nan Yang; Yajing Cai; Ru Zhang; Yan Wu; Weifang Ma; Chuan Fu; Panyue Zhang; Guangming Zhang (Chemosphere, 2023)

Insight into the selection of oxidant in persulfate activation system: The effect of the target pollutant properties - Xuerong Zhou; Eydhah Almatrafi; Shiyu Liu; Huchuan Yan; Dengsheng Ma; Shixian Qian; Lei Qin; Huan Yi; Yukui Fu; Ling Li; Mingming Zhang; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

Advanced treatment and valorization of food waste through staged fermentation and chain elongation - Qingyan Wang; Nan Yang; Yajing Cai; Guangming Zhang; Yan Wu; Weifang Ma; Chuan Fu; Panyue Zhang (Bioresource Technology, 2023)

Organic aerosols in the inland Tibetan Plateau: New insights from molecular tracers - Xin Wan; Pingqing Fu; Shichang Kang; Kimitaka Kawamura; Guangming Wu; Quanlian Li; Shaopeng Gao; Zhiyuan Cong (Science of The Total Environment, 2023)

Data-driven collapse strength modelling for the screen pipes with internal corrosion defect based on finite element analysis and tree-based machine learning - Yudan Peng; Guangming Fu; Baojiang Sun; Jiying Chen; Weiguo Zhang; Meipeng Ren; Heen Zhang (Ocean Engineering, 2023)

A flexible and sensitive 3D carbonized biomass fiber for hybrid strain sensing and energy harvesting - Chiyu Fu; Wenyang Tang; Liangjun Xia; Zhuan Fu; Pei Lyu; Chunhua Zhang; Junyao Gong; Azadeh Nilghaz; Zhigang Xia; Guangming Cai; Weilin Xu (Chemical Engineering Journal, 2023)

Volatile fatty acid production in anaerobic fermentation of food waste saccharified residue: Effect of substrate concentration - Qingyan Wang; Guangming Zhang; Le Chen; Nan Yang; Yan Wu; Wei Fang; Ru Zhang; Xinyi Wang; Chuan Fu; Panyue Zhang (Waste Management, 2023)

Bending Deformation and Ultimate Moment Calculation of Screen Pipes in Offshore Sand Control Completion - Yudan Peng; Guangming Fu; Baojiang Sun; Xiaohui Sun; Jiying Chen; Segen F. Estefen (Journal of Marine Science and Engineering, 2023)
Horizontal wells, extended-reach wells, and multi-branch wells were often used to exploit subsea oil and gas efficiently. However, during the sand control screen completion of those wells, the sand control screen pipe was easily deformed. Failure occurred when passing through the bending section due to the large bending section in the wellbore trajectory. A parametric analysis model of the screen pipe was established based on ABAQUS and Python software under pure bending load first. Then, deformation patterns and mechanisms were identified and discussed. The effects of parameters on the screen pipe bending deformation patterns and the ultimate moment were analyzed. Finally, an empirical formula for calculating the ultimate moment of the screen pipe was established. The results showed that the deformation of the screen pipe was complex, and three deformation patterns were related to the hole parameters. Due to an increase in the diameter and number of circumferential and axial holes, the ultimate moment of the screen pipe gradually decreased, and the circumferential holes had a more significant effect on the ultimate moment than the axial holes. The established empirical formula could accurately calculate the ultimate moment of the screen pipe, and the average difference between the formula and numerical simulation results was 3.25%.

Unveiling the roles of dissolved organic matters derived from different biochar in biochar/persulfate system: Mechanism and toxicity - Xuerong Zhou; Cui Lai; Eydhah Almatrafi; Shiyu Liu; Huchuan Yan; Shixian Qian; Hanxi Li; Lei Qin; Huan Yi; Yukui Fu; Ling Li; Mingming Zhang; et al. (Science of The Total Environment, 2023)

Insights into reactive species generation and organics selective degradation in Fe-based heterogeneous Fenton-like systems: A critical review - Ling Li; Zhuo Yin; Min Cheng; Lei Qin; Shiyu Liu; Huan Yi; Mingming Zhang; Yukui Fu; Xiaofeng Yang; Xuerong Zhou; Guangming Zeng; Cui Lai (Chemical Engineering Journal, 2023)

Efficient chain elongation synthesis of n-caproate from shunting fermentation of food waste - Qingyan Wang; Hao Fu; Guangming Zhang; Yan Wu; Weifang Ma; Chuan Fu; Yajing Cai; Lihui Zhong; Yiwei Zhao; Xinyi Wang; Panyue Zhang (Bioresource Technology, 2023)

Microbial functional communities and the antibiotic resistome profile in a high-selenium ecosystem - Yanmei Sun; Jia Guo; Fu Wei; Xiaohui Chen; Meng Li; Chao Li; Size Xia; Guangming Zhang; Wencai You; Xin Cong; Tian Yu; Shiwei Wang (Chemosphere, 2023)

Coupled carbon structure and iron species for multiple periodate-based oxidation reaction - Ling Xiang; Eydhah Almatrafi; Hailan Yang; Haoyang Ye; Fanzhi Qin; Huan Yi; Yukui Fu; Xiuqin Huo; Wu Xia; Hong Li; Ming Yan; Chengyun Zhou; et al. (Chemical Engineering Journal, 2023)

Genomic characterization and pathogenicity analysis of a porcine deltacoronavirus strain isolated in western China - Zemei Wang; Shuxian Li; Yongheng Shao; Yabin Lu; Chen Tan; Yaru Cui; Guangming Ding; Yuguang Fu; Guangliang Liu; Jianing Chen; Yonghao Hu (Archives of Virology, 2022)

Increasing mortality caused by chronic obstructive pulmonary disease (COPD) in relation with exposure to ambient fine particulate matters: an analysis in Southeastern China - Zhijian Chen; Qiuli Fu; Guangming Mao; Lizhi Wu; Peiwei Xu; Dandan Xu; Zhifang Wang; Xuejiao Pan; Yuan Chen; Xiaoming Lou; Zhe Mo; Xiaofeng Wang; et al. (Environmental Science and Pollution Research, 2021)

Synchronously enhancing biogas production, sludge reduction, biogas desulfurization, and digestate treatment in sludge anaerobic digestion by adding K2FeO4 - Shuli Liu; Guang Yang; Jinwei Fu; Guangming Zhang (Environmental Science and Pollution Research, 2018)

Synchronous granite intrusion and E–W extension in the Cuonadong dome, southern Tibet, China: evidence from field observations and thermochronologic results - Jiangang Fu; Guangming Li; Genhou Wang; Linkui Zhang; Wei Liang; Zhi Zhang; Xiaoqiong Zhang; Yong Huang (International Journal of Earth Sciences, 2018)

The electrical resistivity signature of a fault controlling gold mineralization and the implications for Mesozoic mineralization: a case study from the Jiaojia Fault, eastern China - Kun Zhang; Qingtian Lü; Jiayong Yan; Hao Hu; GuangMing Fu (Acta Geophysica, 2017)

First field identification of the Cuonadong dome in southern Tibet: implications for EW extension of the North Himalayan gneiss dome - Jiangang Fu; Guangming Li; Genhou Wang; Yong Huang; Linkui Zhang; Suiliang Dong; Wei Liang (International Journal of Earth Sciences, 2017)

Longitudinal changes of dopamine transporters in heroin users during abstinence - Shasha Xu; Ying Liu; Yu Li; Yangping Deng; Yiyun Huang; Jie Yuan; Rongbin Lv; Yuankai Wang; Guangming Zhang; Zhirui Guo; Mei Han; Xingdang Liu; et al. (Psychopharmacology, 2015)

Cloning of lipoprotein lipase (LPL) and the effects of dietary lipid levels on LPL expression in GIFT tilapia (Oreochromis niloticus) - Aimin Wang; Guangming Han; Zhitao Qi; Fu Lv; Yebing Yu; Jintian Huang; Tian Wang; Pao Xu (Aquaculture International, 2013)

Characteristic, composition, and sources of TSP investigated by HRTEM/EDS and ESEM/EDS - Yunbo Zhai; Zongmin Fu; Lafang Wang; Guangming Zeng; Caiting Li; Hongmei Chen; Yuanming Lan; Pei Lu (Environmental Monitoring and Assessment, 2012)

Co-degradation with glucose of four surfactants, CTAB, Triton X-100, SDS and Rhamnolipid, in liquid culture media and compost matrix - Guangming Zeng; Haiyan Fu; Hua Zhong; Xingzhong Yuan; Muxing Fu; Wei Wang; Guohe Huang (Biodegradation, 2007)